Legal Analysis of the Authority of the Representative of the Ombudsman RI of North Kalimantan Province in Resolving Reports of Levies at Public Junior High Schools in Tarakan City (Case Study of Public Report Registration No. 0028/LM/VIII/2024/Trk) - Syahruddin, Syahruddin; Tri Bawono, Bambang (Jurnal Hukum Khaira Ummah, 2025)
Abstract. This study aims to analyze the legal authority possessed by the Representative of the Ombudsman of the Republic of Indonesia for the Province of North Kalimantan in handling and resolving reports of alleged levies carried out by the State Junior High School in Tarakan City, with a focus on a case study of the Public Report Registration Number 0028/LM/VIII/2024/TRK. The report relates to the alleged practice of levies that are not in accordance with the provisions of laws and regulations in the basic education environment, which should prioritize the principle of free and non-discriminatory education as mandated in Law Number 20 of 2003 concerning the National Education System. This study uses a normative legal approach by reviewing relevant laws and regulations, report documents, and other secondary data. The analysis was conducted to assess whether the steps taken by the Representative of the Ombudsman of the Republic of Indonesia of North Kalimantan Province in following up on public reports were in accordance with the authority granted under Law Number 37 of 2008 concerning the Ombudsman of the Republic of Indonesia and other implementing regulations. The results of the study show that the Representative of the Ombudsman of the Republic of Indonesia for North Kalimantan Province has exercised its authority legally and proportionally in handling Report No. 0028/LM/VIII/2024/TRK. The examination process was carried out objectively and accountably, resulting in findings of maladministration of levies carried out by the school. The Ombudsman then issued corrective actions in the form of stopping levies and returning funds to parents/guardians of affected students. These corrective actions are a form of implementing the supervisory function of public services in the field of education. The conclusion of this study emphasizes the importance of the Ombudsman's role in maintaining the principles of good governance and protecting people's rights, especially in the education sector.